Heavy Metals Backgrounds In Soils From The Rovigo Province (NE, Italy) - Filippo Trevisan; Gianluca Bianchini; Claudio Natali; Renzo Tassinari; Umberto Tessari (EQA, 2016)
This research is aimed at characterizing the geochemical composition of the alluvial soils in the province of Rovigo in order to identify the provenance of the sediments from which they originated. To carry out this characterization soils were sampled in 5 distinct areas of the province next to the towns of Stienta, Fratta Polesine-Bosaro, Boara Polesine, Concadirame, Lusia. The samples were preliminarily characterized by grain size investigation and then investigated by wavelength dispersion x-ray fluorescence analysis (WDXRF). The data show a considerable compositional variation of the major elements that are strongly influenced by grain size; sandy soils are enriched in SiO2 in relation to the prevalent presence of quartz, while fine soils are comparatively enriched in Al2O3 and K2O that indicate the prevailing presence of clay minerals. Samples from Stienta are similar to soils of the Ferrara province developed by Po river sediments, whereas gradual differences are observed on soils sampled in the middle part of the province in the neighbors of Fratta Polesine-Bosaro. More marked differences are observed in the northernmost areas close to the towns of Boara Polesine, Concadirame and Lusia. This compositional heterogeneity is due to a different contribution from the two river systems feeding the sedimentary basin, i.e. the Po River and the Adige river. Although not systematically, high values in Cr and Ni that characterize the floods of the river Po (Amorosi et al. 2002, Amorosi, 2012; Bianchini et al. 2012; 2013) are also recognized in the northern areas of the province. In the northern soils we also observed comparative enrichment in Pb and Zn. Our preliminary hypothesis proposes that this enrichment in chalcophile elements is a proxy of the sedimentary contribution of Adige river, which is characterized by a drainage basin including mining zones in which sphalerite and galena were extracted in the past centuries.